Contributions of literature in the training of lawyers - Rosner, Tomás (2023)
The current article aims to promote the integration of works of literature into the early years of legal education with the objective of training better legal professionals. Discussed are reasons for and ways by which these disciplines can be integrated with a particular focus on the contribution of poetry. The article reviews how poetry can help improve the quality of writing, oral expression, and how it can help promote creativity and detach us from the automatisms of our attention. In addition, it reviews how poetry can play a fundamental role in survival within the hostile environment of the field of law. Finally, it discusses how poetry may offer tools for dealing with the unknown and exploring areas in which we lack training, as they quickly become elementary in a world that has been transformed into a large question mark.